GENERATION Z VALUE CONFLICTS AND TEAM COLLABORATION IN THE F&B INDUSTRY - I Putu Dharmawan Pradhana; Charles Stefan Winata; Ni Ketut Arniti; Putu Purnama Dewi (Bajang Institute, 2025)
The presence of Generation Z in the workplace is reshaping value configurations and expectations of work culture, particularly in the food and beverage (F&B) industry, which demands a fast pace and intensive coordination. This study aims to narratively investigate how the value conflicts experienced by Generation Z are interpreted, negotiated, and managed within cross-generational team collaboration in two restaurants in Denpasar, namely Resto Cak Asmo and Warung Malabar. The research employs a qualitative approach with a narrative inquiry strategy. Data were collected through in-depth interviews, observation, and documentation involving owners, managers, and Generation Z and millennial employees. Data were analysed interactively using the Miles and Huberman model and the Gioia approach, supported by NVivo 14 software. The findings show that value conflicts mainly arise from tensions between flexibility and discipline, personal ambition and organizational loyalty demands, and direct communication styles versus more subtle hierarchical communication. These conflicts affect the work climate, team cohesion, and the continuity of collaboration, but can be managed through inclusive leadership, adjusted work rules, and cross-generational dialogue spaces. This study contributes to the understanding of generational value conflicts and team collaboration management in highly interactive service sectors.